Literasi Digital Sebagai Fondasi Pendidikan Politik Generasi Muda Era Digital - Yunita Sari; Sunarso Sunarso; Suyato Suyato (Jayapangus Press, 2025)
This study examines the role of digital literacy as a fundamental element in strengthening political education for the younger generation in the digital age. Using a qualitative descriptive method through literature study, this study identifies and analyzes various literature related to digital literacy and political education. The results show that conventional political education is still limited by space and time, while digital-based political education provides broader and more flexible access. Digital literacy is a determining factor in the effectiveness of digital political education because it equips the younger generation with critical thinking skills, the ability to counter disinformation, and the ability to participate responsibly in democratic life. Theoretically, this study contributes to the development of a conceptual model that links digital literacy with political participation. Practically, the results of this study provide recommendations for policymakers and educators in integrating digital literacy into the civic and political education curriculum.